Suicide in Kenyan Universities - Marion K. Mutwiri; Anne G. Wambugu; Jane W. Kinuthia; Lucy Gachenia (European Scientific Journal, ESJ, 2023)
This study examines the prevalence of suicidal thinking, planning, attempts and self-harm and the associated psychological stressors in two Kenyan universities. The participants are undergraduate university students aged (18 -29) years. A convergent mixed method study design was adopted to collect data. Self-administered questionnaire and focus group discussions were carried out among 431 students and six university counselors participated in a three rounds delphi survey. The study instruments were adopted from the Suicide Assessment Five-Step Evaluation & Triage (SAFE-T), Columbia Suicide Severity Rating Scale (C-SSRS), Non-Suicidal Self-Injury Assessment Tool (NSSI-AT) and Emerging Adult Stress Inventory (EASI). A multivariate analysis (MANOVA) was performed. The prevalence rate of suicidal thinking was 17.1%, suicidal planning 5.9%, suicidal attempts 7.8% and self-harm 5.5%. Female students and private university students had high prevalence for all suicidal behaviors. Feeling hopeless and depressed, financial difficult, feeling anxious, family conflicts and academic challenges were psychological stressors compelling emerging adults to suicidal behaviors. The prevalence for suicidal behaviors were similar to that found in other studies carried out in other countries. Suicidal behaviors are associated with mental illness symptoms. This should be taken into account by peers, parents and university counselors to prevent and intervene for suicidal behaviors.